Map ‘Webucation’: Using the World Wide Web for the Continuing Education of Map Librarians - Bauer, Theo; Bühler, Jürg; Crom, Wolfgang (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
This paper introduces the Working Group for Education of the Groupe des Cartothécaires (GdC) de LIBER and gives a progress report of the Group’s activities from 1998 to the present. It also discusses the impact of the Working Group’s decision to put up an Internet platform in terms of the opportunities, achievements, and difficulties encountered when using this particular information platform.